Hermann Bahr Arthur Schnitzler - Briefwechsel, Aufzeichnungen, Dokumente 1891-1931 - Ifkovits, Kurt (Wallstein Verlag, 2018)
Scholarly edition of the correspondence between Hermann Bahr and Arthur Schnitzler, including further documents.